2007
DOI: 10.1016/j.jpainsymman.2006.11.017
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Analgesic Efficacy of Tramadol Contramid OAD Versus Placebo in Patients with Pain Due to Osteoarthritis

Abstract: One thousand twenty-eight (1,028) patients with pain due to osteoarthritis (OA) of the knee were enrolled in this multicenter, randomized, double-blind, parallel study designed to assess the analgesic efficacy and safety of Tramadol Contramid OAD compared to placebo. An open-label phase was followed by a double-blind phase, in which a total of 646 patients were randomized to double-blind treatment with placebo or Tramadol Contramid OAD. Patients were titrated to their optimal dose (200mg or 300 mg), which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 15 publications
1
47
0
Order By: Relevance
“…The wash out of all analgesics including nonopioids may change the efficacy of opioids in osteoarthritis [2,5,10,11,12,18,19,24,27,34]. However, in a subgroup analysis we found only a statistically nonsignificant trend to decreased total dropouts in studies with nonsteriodal antiinflammatory drugs.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…The wash out of all analgesics including nonopioids may change the efficacy of opioids in osteoarthritis [2,5,10,11,12,18,19,24,27,34]. However, in a subgroup analysis we found only a statistically nonsignificant trend to decreased total dropouts in studies with nonsteriodal antiinflammatory drugs.…”
Section: Discussionmentioning
confidence: 70%
“…Another problem in the handling of dropouts can result from an open-label run-in phase [5], because nonresponders to opioids may drop out before the start of the trial period. Although dose titration was conducted after randomization in most trials in this meta-analysis, the dropout rate might be even higher in a real world setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of trials did not report any infectious complications (Roth et al 2000;Caldwell et al 2002;Raja et al 2002;Watson et al 2003;Babul et al 2004;Hale et al 2005;Matsumoto et al 2005;Gana et al 2006;Kivitz et al 2006;Hale et al 2007;Beaulieu et al 2008;Gordon et al 2010). Only 6 out of 18 trials reported infectious complications but their incidence was too low to detect statistically significant differences (see Table 3; (Gimbel et al 2003;Markenson et al 2005;Langford et al 2006;Burch et al 2007;Katz et al 2007;O'Donnell et al 2009). Thus, these data do not permit any firm conclusions regarding the influence of opioids on the development of infectious complications.…”
Section: Relationship Between Opioid Use and Infectious Complicationsmentioning
confidence: 99%